Effect of Nebulisation with Dexmedetomidine versus Magnesium Sulphate on Haemodynamic Response to Laryngoscopy and Intubation and Incidence of Postoperative Sore Throat: A Randomised Clinical Trial - Fateh Pal Singh Gill; Chhaya Suryawanshi (Journal of Clinical and Diagnostic Research)
Introduction: Laryngoscopy and endotracheal intubation are essential procedures in general anaesthesia but can induce sympathetic hyperactivity, leading to transient increase in blood pressure and Heart Rate (HR). This can be particularly risky for patients with co-morbidities. Various agents, including dexmedetomidine and magnesium sulphate, have been studied for their potential to mitigate these responses. Aim: To compare the effects of preoperative nebulisation with dexmedetomidine versus magnesium sulphate on haemodynamic responses during laryngoscopy and intubation and to determine the incidence of Postoperative Sore Throat (POST) in both groups. Materials and Methods: This randomised clinical, double-blind trial was conducted at Dr. D.Y. Patil Medical College, Pune, Maharashtra, India over the period of two years. It involved 80 patients undergoing surgery under general anaesthesia, divided into two equal groups. Group A received nebulisation with dexmedetomidine (1 μg/kg) and Group B received magnesium sulphate (240 mg) diluted in 0.9% normal saline to make a 3 mL solution. Institutional ethical approval and Clinical Trials Registry India (CTRI) registration were obtained. Haemodynamic parameters including HR, Systolic Blood Pressure (SBP), Diastolic Blood Pressure (DBP), Mean Arterial Pressure (MAP) and POST were monitored. Statistical Package for the Social Sciences (SPSS) version 20.0 was used for statistical analysis. Data were analysed using unpaired t-tests for quantitative data and Pearson’s Chi-square test for qualitative data, with significance set at p-value<0.05. Results: Before nebulisation, group A had significantly higher HR and SBP than group B (p-value=0.003 and 0.009, respectively). Postnebulisation, there were no significant differences in HR or SBP between groups. However, group A had lower DBP and MAP during and after intubation and skin incision (p-value <0.001, 0.001, and <0.001 respectively for DBP and 0.030, 0.031 and 0.002 for MAP). Group A had a lower, though not statistically significant (p-value=0.36) incidence of POST compared to group B. Conclusion: Nebulisation with dexmedetomidine and magnesium sulphate both provided effective management of haemodynamic responses during intubation. Both agents decreased the incidence of POST.